The Effect of 1% Povidone Iodine Mouthwash on The Surface Roughness of Zirconia Reinforced Glass Ionomer Cement - Farida, Hifdiyati; Wibowo, Gustantyo Wahyu; Fortuna, Gloria; Nosartika, Isniya (Indonesian Dental Association, 2023)
Introduction: Zirconia reinforced glass ionomer cement is a new generation glass ionomer cement restoration material with the addition of zirconia nanoparticles that is equivalent in strength to amalgam while maintaining ability to release fluoride like conventional glass ionomer cements. Surface roughness can be affected by various factors including the use of mouthwash. Mouthwash that is commonly used during pandemic COVID-19 is 1% povidone iodine. Previous study stated that povidone iodine mouthwash contains alcohol and acidic pH which can decrease the hardness of composite resins. Objective: To determine the effect of 1% povidone iodine mouthwash on the surface roughness of zirconia reinforced glass ionomer cement. Methods: This was a true experimental laboratory research with a pre test and post test control group design. The research samples consisted of 36 samples of zirconia reinforced glass ionomer cement with diameter of 10 mm and height of 2 mm. The samples were divided into two groups: the control group which was immersed in artificial saliva and the treatment group which was immersed in 1% povidone iodine mouthwash for 24 hours. Surface roughness was measured using a surface roughness tester. Data were analyzed using Paired Sample T-Test and Independent Sample T-Test. Results: Paired Sample T-test results showed no significant difference in the surface roughness of the control group between before and after immersion with p value = 0,074 (p>0,05) and a significant difference in the surface roughness of the treatment group between before and after immersion with p value = 0,000 (p<0,05). Independent Sample T-Test results showed significant difference in the surface roughness between the control group and the treatment group with p value = 0,000 (p <0.05). Conclusion: 1% povidone iodine mouthwash has an effect on increasing the surface roughness of zirconia reinforced glass ionomer cement.